KOMPLEMEN DALAM NOVEL ONE TOUCH OF TOPAZ KARYA IRIS JOHANSEN - YUSUF, AKMALIA RAHMATIKA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ This researchÂ  is entitled Complement in Novel One Touch of Topaz by Iris Johansenâ€The aims of this research are to identify and classify the types of complement, and to analyze the function and position of complement in One Touch of Topaz novel by Iris Johansen.In analyzing the data, the writer used the theory of Aarts and Aarts (1982) which divided complement into six types. Aarts and Aarts also describe each function of each complement. The writer analyze the position of complement by seeing the example of complement according to Aarts and Aarts.The method of this research is descriptive method. Descriptive data is a form word rather than a row of numbers. The result of this research found 1.446 sentences has complement which divided into direct object has 305 sentences, indirect object has 67 sentences, benefaktive object has 30 sentences, subject attribute has 332 sentences, object attribute has 23 sentences, and predicator complement has 689 sentences.The other result show that all types of complement found in the novel of One Touch of Topaz by Iris Johansen, each types of complement has one function andÂ  has several position (Direct object has six positions, Indirect object has four position), Benefactive Object has four position, Subject Attribute has two positions, Object Attribute has three positions, and Predicator complement has three positions).Â ----------------------------------------------Keywords : sintax, complement, novelÂ